Comparison of two different transection techniques in liver surgery: an experimental study in a porcine model - Gehrig, Tobias; Manzini, Giulia; Fonouni, Hamidreza; Golriz, Mohammad; Hafezi, Reza; Rahbari, Nuh Nabi; Brand, Karsten; Hinz, Ulf; Müller, Beat P.; Gutt, Carsten N.; Mehrabi, Arianeb (Langenbeck's archives of surgery, 2013)
Postoperative morbidity and mortality after liver resection is closely related to the degree of intraoperative blood loss; the majority of which occurs during transection of the liver parenchyma. Many approaches and devices have therefore been developed to limit bleeding, but none has yet achieved perfect results up to now. The aim of this standardized chronic animal study was to compare the safety and efficacy of the LigaSure™ Vessel Sealing System (LVSS) with the stapler technique, which is one of the modern techniques for transecting the parenchyma in liver surgery.